Avaliação da germinação e vigor na cultura do milho submetidos a diferentes tratamento químicos na semente. - UZUELI, Felipe Feitosa (2021)
The corn (Zea mays L.) is the most produced and consumed cereal, by worldwide population, due to its huge capacity of acceptation and its nutritious values. In order to achieve high levels of productivity when growing, it is necessary the correct and efficient use of insecticides, fungicides and rooters treating seeds, aiming at protecting and stimulating a better development of the plant. The present study had as objective evaluating the influence of different chemical treatments in germination and force of corn seeds, in laboratory conditions. The tested products were - Product 1: insecticide (Clothianidin), Product 2: fungicide (Captana), Product 3: rooter (Composed of anhydrous ammonia, nitrogenous solution, zinc oxide, ferrous sulphate, manganese sulphate, zinc sulphate, cooper sulphate, sodium octoborate and water). The experiment was conducted at University UniCesumar – Centro Universitário de Maringá, in the seeds laboratory and was composed of four treatments, with four repetitions each. T1: insecticide; T2: fungicide; T3: rooter; T4: witness. The tests, which were done to evaluate the force and the germination of the seeds, were measurement of aerial and root parts of the plant, weight of green mass and dry mass of the plant. Besides, it was also obtained results from the percentage of germination of each treatment in the fourth and seventh days. The results were submitted to statistical analysis. Variance analysis: ANOVA, and the averages between treatments compared by the test Scott-Knott to 5% of meaningfulness. The use of rooter in the treatment provided less percentage of germination, resulting in 92 % in the fourth day. However, the development of root system has increased, but it had no influence in the dry mass of the plant. The fungicide and the insecticide have not influenced in the germination, force and development of corn plants.